Development and initial validation of an MDMA/Ecstasy motives assessment. (January 2023) - Sottile, James E.; Macia, Kathryn S.; Wickham, Robert E.; Haug, Nancy A.
Highlights: MDMA use motives differ from those of other substances such as alcohol and cannabis. Four primary motives were identified for MDMA use: Social, expansion, coping, and energy. Social and expansion motives suggest increases in empathy may be a noteworthy predictor of MDMA use. Enhancement and conformity motives for MDMA use did not emerge as significant predictors of MDMA use. Sexual motives for MDMA use did not emerge as a single distinct motive factor. Abstract: Objective: MDMA/Ecstasy motives differ from those of other substances such as alcohol, cannabis, and methamphetamine. Previous literature on alcohol and cannabis use identified social, expansion, enhancement, coping, and conformism as primary motives for use. MDMA/Ecstasy users also report using the drug for increases in self-awareness and energy. The development of an MDMA/Ecstasy use motives assessment has potential to inform treatment interventions and public policy on harm reduction. Method: An MDMA/Ecstasy use motives assessment was developed from alcohol and cannabis motives measures and qualitative feedback from MDMA/Ecstasy users. Participants included an international sample of adults ( N  = 1754) who completed an online questionnaire regarding their motives for using recreational MDMA/Ecstasy. Results: Exploratory and confirmatory factor analysis supported a 4-factor MDMA/Ecstasy motives scale. The four motive scales showed good internal consistency reliabilitySocial (α = 0.88) Expansion (α = 0.81), Coping (α = 0.82), and Energy (α = 0.75). Conformity and Enhancement did not emerge as significant factors. Analyses demonstrated convergent and discriminant validity with relevant constructs including quantity/frequency of use, MDMA use disorder, sensation seeking personality, and positive and negative consequences of use. Conclusions: MDMA/Ecstasy use motives differ from those of other substances due to the distinctly stimulating, emotional, and empathic effects sought by users. By identifying salient MDMA/Ecstasy motives, this study highlights the unique aspects of recreational MDMA/Ecstasy use. This research has utility for informing clinical practice and contributing to public health harm reduction efforts.